Effect of Silver Nanoparticle Size on Efficiency Enhancement of Dye-Sensitized Solar Cells. (28th June 2011) - Photiphitak, Chanu; Rakkwamsuk, Pattana; Muthitamongkol, Pennapa; Sae-Kung, Chaiyuth; Thanachayanont, Chanchana
Abstract : Titanium dioxide/silver (TiO2 /Ag) composite films were prepared by incorporating Ag in pores of mesoporous TiO2 films using a photoreduction method. The Ag nanoparticle sizes were in a range of 4.36–38.56 nm. The TiO2 /Ag composite films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The TiO2 and TiO2 /Ag composite films were then sensitized by immersing in a 0.3 mM N719 dye solution and fabricated for conventional dye-sensitized solar cells (DSCs). J-V characteristics of the TiO2 /Ag DSCs showed that the Ag nanoparticle size of 19.16 nm resulted in the short circuit current density and efficiency of 8.12 mA/cm 2 and 4.76%.